FRI0663 The fine specificity of anti-drug antibody responses to originator and biosimilar infliximab: analyses across five diseases from the 52-week randomized nor-switch study. (12th June 2018) - Goll, G. L.; Bolstad, N.; Iria, I.; Klaasen, R. A.; Jorgensen, K. K.; Olsen, I. C.; Valido, A.; Saavedra, M. J.; Fonseca, J. E.; Lundin, K.; Warren, D. J.; Haavardsholm, E.; et al.
Abstract : Background: Norway's government funded the NOR-SWITCH study to investigate switching from originator infliximab (INX) to biosimilar CT-P13 in Crohn's disease (CD), ulcerative colitis (UC), spondyloarthritis (SpA), rheumatoid arthritis (RA), psoriatic arthritis (PsA) and chronic plaque psoriasis (Ps). Previously, the main analyses have been published 1 . Immunogenicity is associated with treatment failure and is of particular concern in switching 2 . Objectives: To evaluate the consistency and fine specificity of anti-drug antibody (ADAb) responses to INX and CT-P13, in arthritis and IBD patients, after switching from INX to CT-P13. Methods: The study included adult patients with CD, UC, SpA, RA, PsA or Ps 1 . Assays for drug serum levels and ADAb have been described 1 . ADAb positive sera were tested for cross-reactivity to 5 batches of INX and CT-P13. We quantified IgG4 ADAb, testing for functional inhibition. Infliximab peptides were used to compare epitope recognition of positive sera. Immunogenic infliximab-epitopes were identified by ELISA and sera compared across diseases. Results: We tested 15 controls, 15 arthritis, 21 IBD patients. No Ps patients had ADAbs in our study. All 23 anti-CT-P13 and 13 anti-INX sera cross-reacted with INX and CT-P13, respectively. ADAb concentrations to INX or CT-P13 correlated strongly (r values between 0.92 and 0.99, p<0.001 for all experiments, Spearman's correlation test). Sera negative for CT-P13 ADAb (10 healthy controls, 5 RA patients) were also anti-INX negative. IgG4 ADAb in all sera recognized 5 different batches of CT-P13 and INX. All positive sera had similar functional inhibition of CT-P13 or INX TNF-binding capacity, showing reduced binding to CT-P13 in the presence of 5 different batches of CT-P13 and INX. 60%_79% of patients recognized 7 synthetic peptides corresponding to major anti-infliximab epitopes, with no significant differences between CT-P13 and INX ADAb. Three minor epitopes in framework regions of infliximab showed reduced antibody reactivity in 30%_50% of patients. Stratifying by diagnostis, we found two epitopes in the variable and constant heavy-chains of infliximab specifically recognized in IBD patients but not rheumatic patients. Conclusions: ADAbs to INX also recognize CT-P13, with similar epitopes. We found no consistent difference in ADAb epitope specificity between diagnoses. However, two specific minor epitopes are only recognized by IBD patients which might reflect the importance of HLA background for ADAb. References: 1. Jørgensen KK, Olsen IC, Goll GL, et al. Switching from originator infliximab to biosimilar CT-P13 compared to maintained treatment with originator infliximab (NOR-SWITCH): a 52-week randomised double-blind non-inferiority trial. Lancet, 2017Jun 10;389(10086):2304–2316. [Epub 2017 May11]. 2. Dörner T, Jay J. Biosimilars in rheumatology: current perspectives and lessons learnt. Nat Rev Rheumatol2015Dec;11(12):713–24. Disclosure of Interest: G. Goll Consultant for: AbbVie, Biogen, Eli Lilly, Novartis, Pfizer, MSD, Roche, UCB, Boehringer Ingelheim, Orion Pharma, N. Bolstad Consultant for: Pfizer, Orion Pharma, Napp Pharmaceuticals, I. Iria: None declared, R. Klaasen: None declared, K. Jorgensen Consultant for: Tillott, Celltrion, Intercept, I. Olsen Consultant for: Pfizer, A. Valido: None declared, M. Saavedra: None declared, J. Fonseca Consultant for: AbbVie, Ache, Amgen, Biogen, BMS, Janssen, Lilly, MSD, Novartis, Pfizer, Roche, UCB, K. Lundin Grant/research support from: MSD, Consultant for: Takeda, Orion, AbbVie, Rfizer, MSD, D. Warren: None declared, E. Haavardsholm Consultant for: AbbVie, Pfizer, MSD, Roche, UCB, J. Jahnsen Consultant for: AbbVie, Takeda, Janssen, Celltrion, Napp, AstroPharma, Hikma, Orion, Pfizer, T. Kvien Consultant for: AbbVie, Biogen, Eli Lilly, Novartis, Pfizer, MSD, Roche, UCB, Boehringer Ingelheim, Orion Pharma, J. Goncalves Consultant for: AbbVie, Amgen, Biogen, MSD, Pfizer